Managemen Pembelajaran PAKEM di Lembaga TANOKER Kecamatan Ledokombo - Qiptiyah, Titin Mariatul (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2021)
Abstract PAKEM learning originates from the concept of student-centered learning and learning is fun, so that students have the motivation to always learn without instructions and they don't have feelings of heaviness and fear. Thus, the aspect of fun is learning and motivating the students should do exploration, active creation and experiment continuously in the learning process is a significant aspect of the PAKEM learning process. The results showed that: 1) PAKEM Lesson Planning in Tanoker Kec. Ledokombo is not the same as the existing planning in schools that uses a syllabus or lesson plan. However, the planning is in the form of an agenda designed in an institutional meeting and implemented within the next month. This plan puts forward the goals and results of planning. Planning made not only with the ideas of the mentors, but the assisted students also have the opportunity to give ideas and wishes about the implementation planning they want to carry out. 2) Implementation of PAKEM Learning at the Tanoker Kec. Ledokombo is very clear from the various activities carried out, each activity is never separated from a game and the assistants stimulate the participants to be hyper active, creative and make all activities fun so that they can participate in activities from beginning to end, therefore the participants The assistant also pays attention to the learning strategies and methods that will be used. 3) Evaluation of PAKEM Learning at the Tanoker Kec. Ledokombo is carried out at the end of each activity, conducting an evaluation in which there is an evaluation of the process when the activity takes place, an evaluation of the activity when the activity is over and an evaluation of the overall results of the activity when an institutional meeting is held to discuss activities that have been running for one month. Keywords: Learning Management, PAKEM